Dietary Oxalate Loading Impacts Monocyte Metabolism and Inflammatory Signaling in Humans - Kumar, Parveen; Patel, Mikita; Oster, Robert A.; Yarlagadda, Vidhush; Ambrosetti, Adam; Assimos, Dean G.; Mitchell, Tanecia (Frontiers in Immunology, 2021)
Diet has been associated with several metabolic diseases and may impact immunity. Increased consumption of meals with high oxalate content may stimulate urinary calcium oxalate (CaOx) crystals, which are precursors to CaOx kidney stones. We previously reported that CaOx stone formers have decreased monocyte cellular bioenergetics compared to healthy participants and oxalate reduces monocyte metabolism and redox status in vitro. The purpose of this study was to investigate whether dietary oxalate loading impacts monocyte cellular bioenergetics, mitochondrial complex activity, and inflammatory signaling in humans. Healthy participants (n=40; 31.1 ± 1.3 years) with a BMI of 24.9 ± 0.6 kg/m2 consumed a controlled low oxalate diet for 3 days before drinking a blended preparation of fruits and vegetables containing a large amount of oxalate. Blood and urine were collected before (pre-oxalate) and for 5 hours after the oxalate load to assess urinary oxalate levels, monocyte cellular bioenergetics and mitochondrial complex activity, and plasma cytokine/chemokine levels. Urinary oxalate levels significantly increased in post-oxalate samples compared to pre-oxalate samples. Monocyte cellular bioenergetics, mitochondrial complex I activity, and plasma cytokine and chemokine levels were altered to varying degrees within the study cohort. We demonstrate for the first time that dietary oxalate loading may impact monocyte metabolism and immune response in a cohort of healthy adults, but these response are variable. Further studies are warranted to understand oxalate mediated mechanisms on circulating monocytes and how this potentially influences CaOx kidney stone formation. Trial: ClinicalTrials.gov (NCT03877276).